The Role of Punciation in Russian Grammar - Khurramovna, Davlatova Shakhlo (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the role of punctuation in Russian grammar and the history of their occurrence. Punctuation marks as the main component of intonation.